Application of a Hybrid Multi-Criterion Decision-Making Model for Evaluation and Improvement of Nurses' Job Satisfaction - Liu, Chao; Zhou, Huili; Jin, Yanjun; Chuang, Yen-Ching; Chien, Ching-Wen; Tung, Tao-Hsin (Frontiers in Public Health, 2022)
Background. The global shortage and turnover of nurses is a current challenge. Past studies have shown that nurse job satisfaction may ameliorate nurse shortage. Although there are many studies on the criteria influencing nurses' job satisfaction, few have examined the causal relationships and weight of each criterion from a systematic perspective. Objective. Identify the key criteria and causal relationships that affect nurses' job satisfaction, and help nurse leaders identify high-weight, high-impact dimensions and contextualize them for improvement. Methods. The study developed a hybrid multi-criterion decision-making model, which incorporated the McCloskey/Mueller satisfaction 13-item scale (MMSS-13), and the Decision-Making Trial and Evaluation Laboratory and the Importance-Performance Analysis methods The model was used to analyze key factors of nurse satisfaction and their interrelationships based on the experience of 15 clinical nurse specialists. Results. In MMSS-13’s dimension level, “satisfaction with work conditions and supervisor support” (C5) had the highest impact, and “satisfaction with salary and benefits” (C1) had the highest weight. In criteria level, “salary” (C11), “flexibility in scheduling time off” (C24), “maternity leave time” (C31), “opportunities for social contact after work” (C41), and “your head nurse or facility manager” (C51) had high influence under their corresponding dimensions. The “benefits package” (C13) was the top criterion with the highest impact on MMSS-13. Conclusions. This study assessed nurses' job satisfaction from a multidimensional perspective and revealed the causal relationships between the dimensions. It refined the assessment of nurse job satisfaction to help nurse leaders better assess nurse job satisfaction and make strategic improvements. The study found that compensation and benefits had the highest weight in nurses' job satisfaction. Meanwhile, support for family responsibilities and working conditions, and support from supervisors were the cause dimensions of job satisfaction. Among the more detailed criteria, salary, benefits package, maternity leave time, and leadership had a greater impact on nurses' job satisfaction. Nurse leaders should start with these dimensions to achieve efficient improvement of nurses' job satisfaction.